The grain dynamics and structures of debris discs - Yeh, L.-C.; Jiang, I.-G. (EPJ Web of conferences, 2011)
Numerical simulations are used to construct the possible dynamical models of the Vega’s debris disc. New dust grains are assumed to be generated from two clumpy regions. The goal is to test whether an overall circular-symmetric structure can be constructed if the birth places of grains are not uniformly distributed in a ring region.